The housing bubble: an application of the just price. Issue 3 (3rd July 2019) - Berendt, Emil B.
ABSTRACT: The bursting of the U.S. housing bubble in 2006 was one of the precipitating factors in the Great Recession. It also led to renewed attention by economists to the identification of speculative bubbles. An underappreciated set of analytical tools that could be applied to bubbles is the Solidarist understanding of the just price. Employing the thought of Heinrich Pesch, Bernard Dempsey and Oswald von Nell-Breuning, this article develops an empirical approach to the problem of the just price and bubble identification in housing. It concludes that housing prices did violate the conditions for justness. Furthermore, the just price theory can be used by policymakers and analysts to better understand the complexities of modern markets and it addresses several gaps in economists' current understanding of housing and other asset bubbles.